Generalized methodology for conducting industrial toxicity reduction evaluations (TREs) - Java, J. A.; United States. Environmental Protection Agency. Office of Research and Development (Cincinnati, Ohio : The Chemicals and Chemical Product Branch Risk Reduction Engineering Laboratory U.S. Environmental Protection Agency, 1989)
06